2014
DOI: 10.3892/ijmm.2014.1759
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of Sox7 correlates with the upregulation of the Wnt/β-catenin signaling pathway and the poor survival of gastric cancer patients

Abstract: Sox7 is a tumor suppressor gene that plays an important role in the inhibition and progression of cancer. In the present study, we sought to investigate Sox7 expression in gastric cancer (GC) and its association with the Wnt/β-catenin signaling pathway. We also wished to determine its clinicopathological significance and prognostic implications. Sox7 expression and its effects on the Wnt/β-catenin signaling in vitro were assessed by reverse transcription-polymerase chain reaction using the AGS, MKN-45 and GES-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
4
31
0
Order By: Relevance
“…SOX7, a member of the high-mobility group (HMG) transcription factor family, functions as an indispensable co-receptor and plays a critical role in the activation of the canonical Wnt/β-catenin signaling pathway [13,16]. SOX7 is reported to have a tumor-suppressive function in cancers [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…SOX7, a member of the high-mobility group (HMG) transcription factor family, functions as an indispensable co-receptor and plays a critical role in the activation of the canonical Wnt/β-catenin signaling pathway [13,16]. SOX7 is reported to have a tumor-suppressive function in cancers [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…These molecular changes seem to be required to drive early carcinogenesis events in the stomach, a hypothesis that is supported by studies showing that GSK3b phosphorylation and inactivation is associated with cancer progression in gastric cancer [105] . Different studies have shown downregulation-in occasion by unspecified mechanisms-of various negative regulators of the Wnt/b-catenin signaling involved in proliferation and invasion in gastric cancer, including sFRP, Sox7, Sox10, Sox17, HSulf-1, RACK1, ZNRF3 and OSR1 [78,[106][107][108][109][110][111][112][113] . Some Wnt-target genes, such as Dkk-1, Axin, Nemo kinase, etc., have shown to cause inhibition of Wnt signaling itself [114,115] .…”
Section: Loss Of Wnt Repressor Function In Gastric Cancermentioning
confidence: 99%
“…The generation of differential expression profiles from pathological samples can markedly improve cancer biomarker discovery (2). In a previous study, it was demonstrated that Sox7 and β-catenin expression significantly correlated with the depth of invasion, lymph node metastasis, distant metastasis and the TNM (tumor, node and metastasis) stage in GC (3). Overexpression of zinc finger, DHHC-type containing 14 (ZDHHC14) promotes the migration and invasion of scirrhous GC (4).…”
Section: Introductionmentioning
confidence: 99%
“…Ras association domain family member 10 (RASSF10) is an epigenetically silenced tumor suppressor in GC (6). It has previously been demonstrated that the inactivation of tumor suppressor genes and activation of oncogenes serve a significant role in carcinogenesis (3)(4)(5)(6). However, the etiology of GC remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%